A study on active management of third stage of labour as per WHO guidelines: efficacy and complications - Patel, Manthan M.; Jain, Mahima (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: the objective of the study was to evaluate efficacy and complications of AMTSL as per WHO guidelines. Methods: A total of 100 low risk patients assigned randomly at obstetrics department, P.D.U. medical college, Rajkot. Hundred women received i.m. oxytocin 10 IU at the delivery of anterior shoulder of the baby, received uterine massage and delivery of placenta by controlled cord traction and blood loss is measured. Results: Mean blood loss is 119 ml. One case had blood loss >500 ml. Mean duration of third stage of labour is 5.16 minutes. Mean time taken by uterus to contract was 3.8 minutes. Conclusions: AMTSL must be employed for prevention of postpartum haemorrhage (PPH) as advised by W.H.O. AMTSL as a routine protocol significantly brings down incidence of PPH.